The Logistics of Santa: An analysis of a global overnight distribution network - Folina (Guest Author), Haris (Open Schools Journal for Open Science, 2026)
Making toys is not magic, even at the North Pole. Toys are made from real materials like wood, fabric, paint and small electronic parts. These materials must travel safely from all around the world to Santa’s workshop, so nothing breaks or goes wrong. This story looks at a systemic analysis of a global overnight distribution network, explained through Santa’s busy Christmas operation (National Geographic Kids, 2025). We first introduce how planning and organizing materials helps Santa prepare gifts for every child. We then explain why speed, safety, and good teamwork are important for the elves and the reindeer. Here we show that even the biggest Christmas miracle depends on careful planning, smart storage, and fast delivery. In a wider sense, Santa’s case study helps us understand how everyday products move from factories to people’s homes. It shows that good logistics make both Christmas and real-life run smoothly (National Geographic Kids, 2025).